Mobile learning: Perspectives [Aprendizaje móvil: Perspectivas] - Torres Carrion, P. (2017)
From a technical perspective, the future of learning is defined by four axes around which technological and methodological efforts revolve. These axes are mobility, interaction, artificial intelligence and technologybased resources such as augmented reality and games applied to learning. Combining them means creating a model of mobile, interactive and intelligent scenarios that take advantage of the spaces and times available to the learner. The various technologies are already available yet used separately in different educational experiences. It is therefore crucial to combine and integrate them into didactic models wherein the learning attained by students is significant. This article discusses these technologies and proposes an integrative model that enables a framework of reference for didactic work to be established. It concludes by highlighting the need to experiment with technologies and to apply the results to teaching-learning models using alternative interaction schema, and the urgency of having intelligent tutoring systems to make tutoring available on a massive scale.